Assessment of Knowledge About Breast Cancer Screening Among Female Faculty of University of Lahore: Assessment of Knowledge About Breast Cancer Screening Among Female Faculty of University of Lahore - Farhat, Saira; Anwar Faridi, Tallat; Hameed, Sajid; Mehmood , Khalid; Azzam Khan, Muhammad (Pakistan BioMedical Journal, 2022)
Carcinoma of breast is now the most frequent of all cancers, both in male and female malignancies. It is also the fifth leading cause of death from all types of malignancies, and the first among those tumors that kill women. Objective: To assess the knowledge about breast cancer screening among female faculty of University of Lahore, Pakistan. Methods: This was a cross-sectional descriptive research that used a non-probability purposive sampling technique. After getting permission from the participants, data from 356 female faculty members at the University of Lahore was obtained. SPSS version 22 was used to evaluate and enter the data. Results: The findings suggested that female faculty members had a moderate understanding of cancer screening. Even though majority of the participants were aware that mammography is a fundamental and conventional technique for breast cancer screening, they were unaware of when to begin and how frequently it should be done. Respondents also knew what breast self-examination (BSE) and clinical breast examination (CBE) were, but they didn't know when they should begin or how often they should be conducted. Conclusions: In summary, female academic staff at the University of Lahore have a moderate level of knowledge. It is suggested that breast cancer screening methods be made more widely known and educated about through frequent conferences and seminars highlighting the proper age and time for starting BSE, CBE, and Mammography, as well as the need of doing these procedures on a regular basis.